Research on the construction and application of an evaluation index system for vocational school teachers’ professional competency - Zhu, Maoyang; Wang, Lu; Zhang, Chaofeng; Song, Tingxin (Frontiers in Education, 2026)
This study focuses on the evaluation of vocational school teachers’ professional competencies. By addressing current limitations such as narrow evaluation dimensions and single-subject assessment, it integrates diverse theoretical frameworks and policies—including teacher efficacy theory—to construct an evaluation system. Through qualitative interviews and the Delphi method, the system comprises 7 primary indicators, 25 secondary indicators, and 89 tertiary indicators. These encompass: Professional awareness and ethics, Foundational competencies, Theoretical instruction, Practical teaching, Program development, Educational Research and Reform, and Professional development capabilities. A multi-subject collaborative evaluation model was established by integrating subjective and objective weighting methods using the Analytic Hierarchy Process (AHP) and entropy method, and its empirical application was conducted at a vocational school in Hubei Province. Research findings indicate significant disparities in teachers’ professional competencies, with higher scores in the dimension of professional ethics, while competencies in teaching research, practical teaching, and other areas remain relatively weak. Regression analysis reveals that factors such as years of teaching experience and corporate training programs exert differential impacts on competency development. Finally, we propose countermeasures such as tiered training, school-enterprise collaboration, and institutional optimization to provide practical references and support for evaluating vocational school teachers’ competencies and advancing their professional development.